USING A FREQUENCY RADIO ALTIMETER TO DETERMINE BY THE CORRELATION METHOD - Ibragimov, O. M. (Radio Electronics, Computer Science, Control, 2024)
A problem is considered for the terrain roughness root mean square height measurement with the FM radio altimeter. Basic results of theoretical analysis of received signal correlation function in view of the carrier motion parameters influence are presented.